THE EFFECT OF COMBINATION PROGRESSIVE MUSCLE RELAXATION AND MUSIC THERAPY ON BLOOD PRESSURE AND PULSE IN PATIENTS WITH PRIMARY HYPERTENSION IN BABATAN RT 07 RW 01 SURABAYA - Mayangsari, Vandarina Dwi; Septianingrum, Yurike; Khamida, Khamida; Umamah, Farida (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: Hypertension is one of the causes of death in the world, which is also called a